Contrast medium protocols in routine chest CT: a survey study. (March 2022) - Henning, Mette Karen; Aaløkken, Trond Mogens; Johansen, Safora
Background: Administration of contrast medium (CM) is an important image quality factor in computed tomography (CT) of the chest. There is no clear evidence or guidelines on CM strategies for chest CT, thus a consensus approach is needed. Purpose: To survey the potential impact on differences in chest CT protocols, with emphasis on strategies for the administration of CM. Material and Methods: A total of 170 respondents were included in this survey, which used two different approaches: (i) an online survey was sent to the members of the European Society of Thoracic Imaging (ESTI); and (ii) an email requesting a copy of their CT protocol was sent to all hospitals in Norway, and university hospitals in Sweden and Denmark. The survey focused on factors affecting CM protocols and enhancement in chest CT. Results: The overall response rate was 24% (n = 170): 76% of the respondents used a CM concentration of ≥350 mgI/mL; 52% of the respondents used a fixed CM volume strategy. Fixed strategies for injection rate and delay were also the most common approach, practiced by 73% and 57% of the respondents, respectively. The fixed delay was in the range of 20–90 s. Of the respondents, 56% used flexible tube potential strategies (kV). Conclusion: The chest CT protocols and CM administration strategies employed by the respondents vary widely, affecting the image quality. The results of this study underline the need for further research and consensus guidelines related to chest CT.